Mirounga leonina - W. Christopher Wozencraft (Smithsonian Institution Press, 1993)
Mirounga leonina (Linnaeus, 1758). Syst. Nat., 10th ed., 1: 37. TYPE LOCALITY: "ad polum Antarcticum" restricted by Thomas (1911a) to "Juan Fernandez", further restricted by Hamilton (1940) as " Isla Mas a Tierra" [Chile]. DISTRIBUTION: Subantarctic islands, including Macquarie, Kerguelen, S Georgia Isis. STATUS: CITES - Appendix II. SYNONYMS: ansonii de Blainville, 1820; ansonina de Blainville, 1820; coxii Desmarest, 1817; crosetensis Lydekker, 1909; dubia Fischer, 1829; elephantina Gray, 1844; falclandicus Lydekker, 1909; falklandica Peters, 1875; kerguelensis Peters, 1875; macquariensis Lydekker, 1909; patagonica Gray, 1827; proboscidea Peron, 1816; resima Peron, 1816. COMMENTS: Reviewed by Ling and Bryden (1992, Mammalian Species, 391). Published as part of W. Christopher Wozencraft, 1993, Order Carnivora, pp. 279-348 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 330, DOI: 10.5281/zenodo.7359191